2007
DOI: 10.1016/j.mito.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the mitochondrial enzyme carbamyl-phosphate synthetase I predisposes children to increased pulmonary artery pressure following surgical repair of congenital heart defects: A validated genetic association study

Abstract: Increased pulmonary artery pressure (PAP) can complicate the postoperative care of children undergoing surgical repair of congenital heart defects. Endogenous NO regulates PAP and is derived from arginine supplied by the urea cycle. The rate-limiting step in the urea cycle is catalyzed by a mitochondrial enzyme, carbamoyl-phosphate synthetase I (CPSI). A well-characterized polymorphism in the gene encoding CPSI (T1405N) has previously been implicated in neonatal pulmonary hypertension. A consecutive modeling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
(15 reference statements)
1
28
0
7
Order By: Relevance
“…In accordance with our results, it has been reported a protective role of the A-allele toward persistent pulmonary hypertension of the newborn15, pulmonary hypertension following surgical repair of congenital heart defects26, and hepatic veno-occlusive disease after bone marrow transplantation23. Moreover, the haplotype formed by the SNPs of CPS1 rs715 and rs1047891 (p.Thr1406Asn) yield a protective association with decreased risk of coronary artery disease in women35.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with our results, it has been reported a protective role of the A-allele toward persistent pulmonary hypertension of the newborn15, pulmonary hypertension following surgical repair of congenital heart defects26, and hepatic veno-occlusive disease after bone marrow transplantation23. Moreover, the haplotype formed by the SNPs of CPS1 rs715 and rs1047891 (p.Thr1406Asn) yield a protective association with decreased risk of coronary artery disease in women35.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that the A-allele may confer an advantage in terms of NO production, especially under conditions of environmental stress15. Previous studies demonstrated the association of the CPS1 p.Thr1406Asn genotype with clinical situations where endogenous NO production is critically important, such as persistent pulmonary hypertension of the newborn15, pulmonary hypertension following surgical repair of congenital heart defects26, and hepatic veno-occlusive disease after bone marrow transplantation23.…”
mentioning
confidence: 99%
“…In subjects who are homozygous for the A allele the nitric oxide metabolite concentration was lower than in those who are homozygote for C allele or heterozygous (Summar et al, 1995). The p.Thr1406Asn amino acid substitution results in a significant change of CPS1 enzymatic function (Canter et al, 2007) with a reported 30-40% difference in enzyme activity (Summar et al, 1995). The polymorphism is located at a variable position in the MSA, and asparagine at 1406 is found in homolog sequences.…”
Section: Discussionmentioning
confidence: 96%
“…In the CPS1 group, for example, we are alert to the possibility of increased incidence of pulmonary hypertension or a pathologic condition involving compromised NO production. 32 In the CTX group, the development of accelerated atherosclerosis, abnormal lipid profiles, and the dietary affect of cholestanol 33 are matters for future follow up.…”
Section: Population Screening In a Druze Communitymentioning
confidence: 99%